The revenue and base effects of local tax hikes: Evidence from a quasi-experiment - Thushyanthan Baskaran (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper studies the revenue and base effects of local property and business tax hikes using a natural experiment in the German state of North Rhine-Westphalia (NRW). Due to a reform of the local equalization scheme in 2003, a set of municipalities in NRW increased their local tax rates by one to two percentage points while the remaining municipalities kept their rates constant. Using this variation across municipalities and over time to implement a difference-in-differences design covering the period 1995-2010, I find that property tax hikes have a revenue elasticity of unity and no adverse base effects. Business tax hikes have no discernible base effects but also no statistically significant effect on revenues. Furthermore, the results suggest that the tax hikes have no effect on broader economic outcomes such as local employment, firms wage bill, and property prices. Overall, increasing local tax rates by one to two percentage points does not seem to affect the local economy adversely.
Keywords: H20; H71; H77; 330; tax hikes; tax base effects; local business taxes; local property taxes